MOLECULAR DYNAMICS STUDIES ON THE STRENGTH PREDICTION OF INTERFACE BETWEEN AL-AL4C3 IN METAL MATRIX NANOCOMPOSITES - Haryadi, Deni; Rudianto, Haris; Yamin, Mohamad (Universitas Gunadarma, 2020)
In this study, molecular dynamics simulations (MD) will be applied to modelling the Al4C3-aluminum interface in aluminum nanocomposite, Al4C3 is an interface that results from the shaker mill process which becomes a bridge that plays an important role in Carbon particles with Aluminium Matrix and Based on observations from the TEM characterization, it is found that the relationship between Al orientation to Al4C3 is (111) (002) (220). The characteristics of the interface between Aluminum matrix and Al4C3 will be analyzed using uniaxial tension and shear test simulation. The atomic potential used in this simulation is the embedded atomic method (EAM) for Al, empirical-order intermolecular potential (AIREBO) for C and lennard jones for the reaction of Al-C atom. The result shows that, the interface orientation is Al matrix (002) || Al4C3 (003) has the highest interface strength compared to Al matrix (111) || Al4C3 (003) and Al matrix (200) Interface orientation || Al4C3 (003). Results from the molecular dynamics simulations are also discussed with analytical results obtained experimental